Effects of Exercise and Sports Intervention and the Involvement Level on the Mineral Health of Different Bone Sites in the Leg, Hip, and Spine: A Systematic Review and Meta-Analysis - Oliveira, Thiago P. [UNESP]; Espada, Mário C.; Massini, Danilo A. [UNESP]; Robalo, Ricardo A. M.; Almeida, Tiago A. F. [UNESP]; Hernández-Beltrán, Víctor; Gamonales, José M.; Castro, Eliane A. [UNESP]; Pessôa Filho, Dalton M. [UNESP] (MDPI, 2023)
The current study analysed whether the osteogenic stimuli of exercises and sports have an independent effect on bone mineral density (BMD). Studies with a design having two different cohorts were searched and selected to distinguish the effect due to long-term involvement (i.e., athletes vs. non-active young with good bone health) and due to the planning of intervention (i.e., pre- vs. post-training) with exercises and sports. Moreover, only studies investigating the bone sites with a body-weight support function (i.e., lower limb, hip, and spine regions) were reviewed, since the osteogenic effects have incongruous results. A meta-analysis was performed following the recommendations of PRISMA. Heterogeneity (I2) was determined by combining Cochran’s Q test with the Higgins test, with a significance level of α = 0.05. The studies reporting the effect of involvement in exercise and sports showed high heterogeneity for the lower limb, total hip, and spine (I2 = 90.200%, 93.334%, and 95.168%, respectively, with p < 0.01) and the effect size on sports modalities (Hedge’s g = 1.529, 1.652, and 0.417, respectively, with p < 0.05) ranging from moderate to high. In turn, the studies reporting the effect of the intervention planning showed that there was no heterogeneity for the lower limb (I2 = 0.000%, p = 0.999) and spine (I2 = 77.863%, p = 0.000); however, for the hip, it was moderate (I2 = 49.432%, p = 0.054), with a low effect between the pre- and post-training moments presented only for the hip and spine (Hedge’s g = 0.313 and 0.353, respectively, with p < 0.05). The current analysis supported the effect of involvement in exercise and sports by evidencing the effect of either weight-bearing or non-weight-bearing movements on BMD at the femoral, pelvic, and lumbar bones sites of the athletes when comparing to non-athletes or non-active peers with healthy bones. Moreover, the effect of different exercise and sports interventions highlighted the alterations in the BMD in the spine bone sites, mainly with long-term protocols (~12 months) planned with a stimulus with high muscle tension. Therefore, exercise and sport (mainly systematic long-term practice) have the potential to increase the BMD of bones with body-weight support beyond the healthy values reached during life phases of youth and adulthood.
Keywords: bone; health; physical activity; sports